Literature Review: Sexually Transmitted Diseases In Prisoners - Elsa fitri Ana; Chanda Paramitha Bherty; Durotul Yatimah; Retno Dwi Lestari; Niken Grah Prihartanti; Mudhawaroh, Mudhawaroh (Jurnal EduHealth, 2024)
Introduction: The prevalence of sexually transmitted diseases is higher among prison populations compared with the general population. Prisoners have high rates of chronic conditions, and the experience of detention (exposure) generally has a greater impact on health than the length of detention. Aims: This article discusses some of the most important infectious diseases found in prisons. Methods: All research was conducted using a cross-sectional study design and published after 2018. Results: We found HIV, HBV, HCV and Syphilis as common sexually transmitted diseases in prison. HIV incidence was found to be 3.7%, 0.4%, 1.4%, 4.1%, and 1.6%. The incidence of hepatitis B in this study was 3.3%, 6.3%, 16.4%, and 41.5%, while the incidence of hepatitis C was 2.3%, 6.2%, 11.6%, 14.3%, and 18.9%. Syphilis was found in 7.0%, 22.1%, 1.1%, 2.0%, 0 and 1.2%. Conclusion: The incidence of sexually transmitted diseases found in the incarcerated population is high.